OPTIMALISASI PERAN MASYARAKAT DALAM UPAYA MITIGASI BENCANA UNTUK MEWUJUDKAN DESA TANGGUH BENCANA DI DESA SUKADANA - Rahman, Rayn Ade; Hakikah, Zahiratul; Putri, Nurliana Andini; Aupiya, Sayidatul; Mariana, Ana; Nafizatunni’am; Aidi, Ahmad Pajar; Maulan, Muhammad Galih; Fahrianty, Nyimas Alvira; Rosyida, Khairul; Misbahuddin (Universitas Mataram, 2024)
Field Study for Empowering of Village Communities (FS-EVC/KKN-PMD) is a program of community service carried out in an interdisciplinary, institutional, and partnership manner as an implementation of the university's tri dharma. Mataram University manages the implementation of Community Empowerment KKN in villages with various themes according to the village's issues or potential. The Disaster Resilient Village (DESTANA) theme is one of the themes developed in collaboration with the Regional Disaster Management Agency (BPBD) of West Nusa Tenggara Province. DESTANA KKN aims to assist village communities in preparedness and resilience against both natural and non-natural disasters. Sukadana Village in Pujut Sub-district, Central Lombok, is one of the targets of the DESTANA. Therefore, the KKN program and activities are aimed at assisting the village towards becoming a primary resilient village in five components of village resilience, namely: Quality and Access to Basic Services, Disaster Management Regulations and Policies, Prevention and Mitigation, Emergency Preparedness, and Recovery Preparedness. Based on a survey of the five components of village resilience, Sukadana Village in Pujut Sub-district, Central Lombok, is vulnerable to drought. Therefore, the implementation of activities is focused on tree planting in Bukit Kemal Muluq and disaster response socialization to the community. In addition, to sustain disaster resilience activities, a Village Climate Awareness Institution (LMSID) has been formed.